Penyusunan Modul Ajar Bahasa Indonesia Berdiferensiasi dalam Implementasi Kurikulum Merdeka di Sekolah Indonesia Kota Kinabalu - Ersila Devy Rinjani; Fitria Martanti; Ulya Himawati; Nugroho Prima Indra Jaya; Tahta Al Fina (Jurnal Pengabdian Kepada Masyarakat, 2025)
The problem faced by the partner, Sekolah Indonesia Kota Kinabalu, is that most teachers are still not able to compile the Indonesian Teaching Module in a differentiated manner. The main purpose of this service is the preparation of differentiated teaching modules on Indonesian subjects for teachers in this school. The method used in this service is the participatory rural appraisal (PRA) model. This method allows the active involvement of partners involved in the implementation of this service. This method was chosen because it is based on the reason that the improvement can be made through the active participation of the partners involved. Based on the results of the community service that has been carried out, it can be seen that the results of the implementation of the activities obtained include the improvement of teachers' abilities in the preparation of differentiated Indonesian Teaching Modules. Another improvement is the ability of teachers to implement creative and innovative learning and differentiated learning. In addition, this service activity can also strengthen the collaboration network Community Learning Center (CLC) teachers in Kota Kinabalu.